Webometric Analysis of Web Presence and Links of SAARC Countries - M., Vijayakumar; Kannappanavar, B.U.; K.T., Santosh Kumar (DESIDOC Journal of Library & Information Technology, 2011)
This study focuses on the identification of web presence and their links among SAARC countries. Theresearch explores that India possesses maximum of 14, 10, 00, 000 webpages; 58, 20, 000 external links;1, 18, 00,000 internal links; and 9, 83, 00,000 over all links. In case of web impact factor of external andinternal links, Sri Lanka claims highest and for over all links once again India claims highest. One can notethat, except India no SAARC country possesses all sub-domains, but these possess only a few sub-domainslike .edu, .gov, .net, and .org. When analysis of the links was done, it was found that Pakistan has a maximumof 3,610 links to India as compared to other SAARC countries. India once again claims top position amongthe SAARC countries for Wiser ranking. http://dx.doi.org/10.14429/djlit.32.2.1409